The Impact of Smurf Attack on Web Server In Communication Network And Its Preventions - Sri Hartanto (International Journal of Sustainable Applied Sciences, 2023)
The Smurf Attack is a type of Distributed Denial of Service (DDoS). Generally, DDoS attacks that paralyze the Web server computer as the target of the attack so that it cannot provide services. Smurf Attacks send a Gropher Communication Packet request (PING Request) to all addresses in a communication network by broadcast. All computers within the broadcast address will answer the PING request. If a network system has many computers (devices) and PING is broadcast continuously, the network system can be met by responses from PING requests, which results in the bandwidth of the communication network being reduced or even exhausted, so that the communication network becomes slow and paralysed. In order to identify how a Smurf Attack occurs on a Web Server computer, in this research, a simulation of a Smurf Attack is carried out on a Web Server computer in a Local Area Network (LAN) and observes the number of packets received by a Web Server computer to determine the performance of the Web Server computer after receiving a Smurf Attack.